PENGARUH PENGGUNAAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA MELALUI PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA - Riska Ashar Luthfia Erva; Ahniasari Rosianawati; Pardimin; Ana Fitrotun Nisa; Muhammad Irfan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the effect of using mathematics learning modules based on ethnomathematics through a scientific approach to the accurate material of students' learning outcomes. The study was conducted for the fifth-grade students in one of the Elementary schools, which was located in Rongkop Gunungkidul in the academic year of 2021/2022. The subject of the study covers 16 students, which consist of 7 male students and 9 female students. The design of the study was qualitativequantitative research. Techniques of data collection used were tests and questionnaires. Techniques of data analysis used were qualitative and quantitative analysis. The result of the study showed the effect of using a mathematics learning module based on ethnomathematics through a scientific approach on the accurate material of students' learning outcomes. The total number of students who passed the test from 6 students was 37.5% increasing to 14 students (93.75%). The average score of students' learning outcomes increased from 79.94 to 95.44. The result of students' questionnaires showed that 87.5% of 14 students strongly agreed and 12.5% of 2 students agreed on the use of the mathematics learning module based on ethnomathematics.